2013
DOI: 10.2147/opth.s53223
|View full text |Cite
|
Sign up to set email alerts
|

Retinal thickness changes after phacoemulsification

Abstract: PurposeTo determine the effect of phacoemulsification on macular volume and thickness using spectral domain optical coherence tomography examinations.MethodsTwenty-seven eyes of 27 subjects who underwent phacoemulsification were studied. All nine areas of the macula were examined by spectral domain optical coherence tomography preoperatively and 2 months postoperatively. Effective phacoemulsification time and absolute phacoemulsification time were also recorded.ResultsThere were statistically significant diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
(30 reference statements)
1
12
0
Order By: Relevance
“…13 Optical coherence tomography plays an important role in subclinical macular oedema diagnosis, as it can detect small increases in macular thickness. 5,6,7,8,9,12,14,15,16,17,18 In this study, a significant increase in the macular thickness had been reported by OCT in all areas after uneventful phacoemulsification cataract surgery. The changes differed according to the duration after the operation and the involved area or sector in the macula.…”
Section: Discussionsupporting
confidence: 54%
“…13 Optical coherence tomography plays an important role in subclinical macular oedema diagnosis, as it can detect small increases in macular thickness. 5,6,7,8,9,12,14,15,16,17,18 In this study, a significant increase in the macular thickness had been reported by OCT in all areas after uneventful phacoemulsification cataract surgery. The changes differed according to the duration after the operation and the involved area or sector in the macula.…”
Section: Discussionsupporting
confidence: 54%
“…In phacoemulsification, the mechanical effects resulted from ultrasound energy and liquid regulation in that surgery due to compression reaction and hypoxia in the tissue. 15 One week after phacoemulsification, the thickness of peripapillary RNFL increased in every quadrant (superior, inferior, temporal, and nasal) and in the mean of all quadrants, even though the differences were not statistically significant. The increase of peripapillary RNFL thickness was greater in glaucoma group compared to non-glaucoma.…”
Section: Yoles Et Almentioning
confidence: 84%
“…In the present study, an approximately 20 μ m mean increase in CFT was significantly noted at 1 month after cataract surgery. A previous study has shown an increase in retinal thickness of approximately 21.7 μ m after cataract surgery in healthy eyes [ 25 ]. Thus, a 20 μ m increase in CFT in our patient may not be an unusual finding.…”
Section: Discussionmentioning
confidence: 99%